Teknologi Tenda Militer Portabel Berbasis Tenaga Surya Dalam Mobilisasi Taktis Tempur - Aritonang, Sovian; Fajri, Zaidan Al; Azida, Putry Wanda; Sandri, Azzahra; Dintyra, Muhammad Daffa (Fakultas Teknik UMSU, 2024)
Indonesia's extensive geography, spanning from Sabang to Merauke, provides an uninterrupted solar energy supply, thanks to its prolonged daylight hours. This presents an excellent opportunity for the country to embrace renewable and sustainable energy, with solar power being a convenient option given Indonesia's tropical climate. The conversion of solar heat into electrical energy is an attractive proposition, allowing for the use of portable solar panels to power military vehicles while minimizing reliance on fossil fuels. Efficient energy storage solutions are needed to convert solar thermal energy into electrical energy, and sodium batteries are a more potent and eco-friendly option. Portable solar panels also offer an energy source for various military operations, such as powering tents and charging communication equipment. By incorporating solar energy into their operations, the Indonesian army can increase their capabilities while reducing their reliance on conventional energy sources. In conclusion, harnessing the abundant sunlight and tropical climate in Indonesia through portable solar panels and sodium-based batteries is a dependable and sustainable solution to meet the energy needs of military operations. This approach enables Indonesian soldiers to carry out their missions efficiently while minimizing environmental impacts.